Legal Analysis Of Judge's Decision On The Imposition Of Criminal Sanctions For Placement Of Illegal Indonesian Migrant Workers Study Of Decision No. 107/PID.SUS/2024/PN RHL - Bambang Hermanto; Sriono Sriono; Nimrot Siahaan (CV. AFDIFAL MAJU BERKAH, 2025)
The method used in this study is normative legal research, namely research on problems by looking at the sources of applicable regulations related to the title of Legal Analysis of Judge's Decisions Regarding the Imposition of Criminal Sanctions for the Placement of Illegal Indonesian Migrant Workers Study of Decision No. 107 / PID.SUS / 2024 / PN RHL. The legal policy stipulated in this decision is based on Article 81 of Law of the Republic of Indonesia Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers, as well as other relevant laws and regulations, so that the results of the decision try and determine that the defendant has been proven legally and convincingly guilty of committing the crime of